PENGEMBANGAN E-LKPD BERBASIS GAME TRUTH OR DARE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI-2 SMA NEGERI 8 PADANGSIDIMPUAN - Ardiana, Nunik; Lubis, Roslian; Pasaribu, Dahlia (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
The purpose of this study was to produce E-LKPD based on truth or dare game on trigonometry material of sine and cosine rules. This study used the ADDIE development model consisting of 5 phases, namely analysis, design, development, implementation and evaluation. However, research was conducted only the implementation phase. The subjects of this study were 27 students. Validity was obtained based on the validator's assessment. Practicality was obtained based on the results of observer observations of student activities. Effectiveness was obtained based on students' pretest and posttest scores. The results of the analysis of E-LKPD based on truth or dare game on trigonometry material of sine and cosine rules have a validity percentage of 87.91% with very valid criteria. The practicality of E-LKPD based on truth or dare game has a practicality percentage of 93.5%, with a very practical category. The effectiveness of E-LKPD based on truth or dare game is 81.134%, with very effective criteria. Conclusion of the research, the development of E-LKPD based on the truth or dare game was be valid, practical, and effective in applying trigonometry learning of the rules of sines and cosines for the eleventh grade students.